Of scrapes and scratches a preliminary study on the use-wear of porcelain sherds from structure A, Pinagbayanan, San Juan, Batangas, Philippines - Kintanar, Andrea Natasha E. (Hukay, 2014)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/4367/3963